2022
DOI: 10.1186/s12877-022-02783-4
|View full text |Cite
|
Sign up to set email alerts
|

A multifactorial interdisciplinary intervention to prevent functional and mobility decline for more participation in (pre-)frail community-dwelling older adults (PromeTheus): study protocol for a multicenter randomized controlled trial

Abstract: Background Age-related decline in physical capacity can lead to frailty, associated with an increased vulnerability to adverse health outcomes and greater healthcare utilization. In an aging population, effective strategies to prevent physical decline and frailty, and preserve independence are needed. Prevention programs for vulnerable community-dwelling older adults are, however, often not yet established and implemented in routine practice. Research on the feasibility, implementation, and (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Our study does not support the combined strategies being better than either strategy alone, and suggests that long-term (ie, beyond 6 months) positive effects on frailty are 4 or have involved intensive supervised activity several times a week. 43 There are several trials of similar combinations of interventions yet to be published, [44][45][46][47][48][49][50] which are needed to further clarify the effectiveness of such interventions in preventing and reversing frailty. 51 Applying the NNT to our data showed that for one pre-frail person to become robust in the SC group at 6 months after the intervention, 6 (95% CI 3-19) would need to be treated, while for the SAYGO group, 9 (4-289) would need to be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Our study does not support the combined strategies being better than either strategy alone, and suggests that long-term (ie, beyond 6 months) positive effects on frailty are 4 or have involved intensive supervised activity several times a week. 43 There are several trials of similar combinations of interventions yet to be published, [44][45][46][47][48][49][50] which are needed to further clarify the effectiveness of such interventions in preventing and reversing frailty. 51 Applying the NNT to our data showed that for one pre-frail person to become robust in the SC group at 6 months after the intervention, 6 (95% CI 3-19) would need to be treated, while for the SAYGO group, 9 (4-289) would need to be treated.…”
Section: Discussionmentioning
confidence: 99%